One New Royleanumoate from Teucrium royleanum Wall. ex Benth - Shabir Ahmad; Riaz Ullah; Naser M. AbdElsalam; Hassan Fouad; Ahtaram Bibi; Muhammad Tariq Jan; Anwar Ali Shad; Muhammad Arfan (The Scientific World Journal)
One new royleanumoate, a benzene ester (1), has been isolated from T. royleanum Wall. ex Benth along with two known compounds, namely, 3,4-dihydroxymethyl benzoate (2) and oleanolic acid (3). The structure elucidation of the isolated compounds was established on two-dimensional (2D) NMR techniques including heteronuclear multiple bond correlation (HMBC), heteronuclear multiple quantum Coherence (HMQC), and correlation spectroscopy (COSY) experiment.